Qu’est-ce que « manager » ? - Salvatore Maugeri (La Nouvelle Revue du Travail)
This issue of Matériaux (Materials) derives from a series of 2007 interviews with Jean, a 44 year old Gadzarts engineer and former executive in a multinational. Jean had just been fired and totally changed directions by becoming a cabinetmaker. He was asked about his training, his vision of things and management experience, all against the background of his worries about being able to create the kind of space that senior managers at this level would normally enjoy in terms of their relations with both the top and bottom of the hierarchical pyramid. This was a valuable interview talking about how managers translate strategic orientations to the operational unit level, and also about the tensions provoked on such occasions as a result of hegemonic financial thinking.